School leadership in the 21st century : developing a strategic approach - Davies, Brent, 1949-; Ellison, Linda; Bowring-Carr, Christopher, 1934- (RoutledgeFalmer, 2005)
This revised edition of a popular text takes into account new Government initiatives on competency frameworks to guide the development of teachers and those in middle and senior management.